2001
DOI: 10.1042/cs20000163
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone abolishes the angiotensin II-mediated potentiation of endothelin-1 in bovine bronchi

Abstract: Angiotensin II potentiates methacholine-evoked bronchoconstriction both in bovine airways in vitro and in asthmatic patients in vivo. Angiotensin II also potentiates endothelin-1-evoked contractions in vitro, but fails to alter such contractions in vivo. One possible confounding factor in patients is their use of inhaled corticosteroids. Accordingly the present study examined the effects of hydrocortisone (cortisol) on contractions evoked by methacholine and endothelin-1 in the presence and absence of angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…That study found that this cytokine response was mediated by AngII and was inhibited by losartan, an AT 1 receptor antagonist. This supports a role for AngII in inducing bronchial constriction via the AT 1 receptor [32]. This supports a role for AngII in inducing bronchial constriction via the AT 1 receptor [32].…”
Section: Ras and Copdsupporting
confidence: 77%
“…That study found that this cytokine response was mediated by AngII and was inhibited by losartan, an AT 1 receptor antagonist. This supports a role for AngII in inducing bronchial constriction via the AT 1 receptor [32]. This supports a role for AngII in inducing bronchial constriction via the AT 1 receptor [32].…”
Section: Ras and Copdsupporting
confidence: 77%
“…Although AngII can act as a weak bronchoconstrictor through its AT 1 R, it can act synergistically with endothelin-1 (ET-1) to evoke more powerful contractions in bronchial bovine smooth muscles [103,104]. This mechanism might be mediated indirectly by leukotrienes [105].…”
Section: Angii Bronchial Hyperresponsiveness and Airway Remodelingmentioning
confidence: 98%
“…The present study confirms that repeated sensitization results in pulmonary tissue injury including proliferation of smooth muscle cells in the trachea and alveoli, as evidenced by the stained tissue sections and morphometric measurements. Although AngII can act as a weak bronchoconstrictor throughits AT1R, it can act synergistically with endothelin-1 to produce more powerful contractions in bronchial bovine smooth muscles [19,20]. AngII can activate phospholipase A2 and the release of arachidonic acid from membrane phospholipids [21].…”
Section: Discussionmentioning
confidence: 99%